Linguistic Landscape Projects as English Teaching and Learning Resources: A Review - Anna Marietta da Silva (Scope : Journal of English Language Teaching, 2023)
As the interest for linguistic landscape research has grown a lot in the past few decades, and so is the enthusiasm for taking advantage of linguistic landscape in language and subject-content classrooms. This paper aims at providing informative and valuable summary of works that have promoted the linguistic landscape as one of the English teaching and learning resources. Hence, it includes only papers that have specifically focused on advocating the benefits of linguistic landscape for English teaching and learning within the last ten years. The review is divided into several sections that explain the targeted participants, goal, method, advantages and several critical notes concerning the implementation of linguistic landscape projects. Suggestions for future review and studies on linguistic landscape are also provided.